(untitled) (Annals of Medical Research, 2021)
Aim: Alkaline phosphatase is perhaps the most important biochemical marker used in the diagnosis and follow-up of metabolic bone disease or osteopenia of prematurity (OP). The aim of this study was to investigate the percentiles of alkaline phosphatase (ALP) levels in premature infants compared to gestational age and to determine cut-off values for the diagnosis of osteopenia.Material Methods: All ALP results sent to our biochemistry laboratory between 2013-2018 were evaluated retrospectively. Of the total 2476 results, 1830 (74%) were found to belong to a separate infant born before 30 weeks of gestation. The results and demographic data of the patients whose clinical information could be reached were statistically analyzed.Results: The mean birth weight of the infants included in the study was 995 g±254 (450-1500 g) and the mean gestational week was calculated as 27±1.7 (24-29,6 weeks). The average alkaline phosphatase level was 510±225 U/L [median: 458 IU/L (159-1554)]. In serum ALP levels; 160.8 IU/L value 5. Percentile, 203 IU/L 10. percentile, 290 U/L 25. percentile 421 IU/L 50. percentile, 583 U/L 75. Percentile, 819 U/L formed 90th percentile and 969 U/L formed 95th percentile. Separate percentiles were also calculated for each gestational week interval.Conclusion: Although the infants included in the study were hospitalized premature infants, this is the reference range study with the largest number of patients in our country. Although the data is retrospective, these percentiles may be helpful in the evaluation and the diagnosis of osteopenia in premature infants.Keywords: Preterm infant; alkaline phosphatase; osteopenia; phosphorus.